Nontoxigenic Vibrio cholerae Septicemia in an Immunocompromised Patient - Kamran Kadkhoda; Heather Adam; Matthew W. Gilmour; Gregory W. Hammond (Case Reports in Infectious Diseases)
We report a recent case of non-O1, non-O139, nontoxigenic Vibrio cholerae septicemia in a post-liver-transplant immunocompromised patient associated with prior seafood consumption. Non-O1, non-O139 V. cholerae strains have been reported in several cases of extraintestinal infections and seem to be emerging infectious agents especially in patients with immunocompromising conditions.